Production of cyclodextrin glucanotransferase (CGTase) from Bacillus stearothermophilus HR1 in shake flasks - Wong, Tien Ee; Abd. Rahman, Roshanida; Illias, R. M.; Md. Salleh, Madihah; Hassan, Osman; Kamaruddin, Kamarulzaman; Nik Mahmood, Nik Azmi (Universiti Malaysia Sabah, 2003)
The objective of this paper is to increase CGTase production from Bacillus stearothermophilus HR1 by optimization of medium formulation and fermentation variables. Central composite factorial design was used to achieve this purpose. Interpretation of results was carried out using the analysis of variance (ANOVA) and analyzed using the 3-D response surface plot. The parameters studied in the medium formulation were concentration of sago starch, peptone casein, K2HPO4, CaCl2 and initial pH of the medium. Increase in the enzyme activity up to 14.20 U/ml, with the regression constant (R2) of 0.9486. For optimization of pH and agitation speed, culture was incubated in shake flasks at 55C. CGTase produced was 16.15 U/ml, with a regresssion of 92.34%. An increase of 3.8 fold in CGTase activity was obtained after optimization. We have successfully optimized the production of CGTase from Bacillus stearothermophilus HR1 using experimental design approach.